The Effect of Giving Turmeric and Honey Boiled Water on the Incidence of Flour Albus in D-III Midwifery Students at the Indonesian Strada Institute of Health Sciences - Heri Saputro; Jumiati Ester Binti Daud (Open Access Health Scientific Journal, 2022)
Background: Vaginal discharge (flour albus) is a white fluid that comes out of the vagina in excess and can cause complaints such as itching and burning in the intimate area. Efforts in handling flour albus can use traditional medicine, namely turmeric and honey. This study aimed to determine whether there is an effect of giving turmeric and honey boiled water to the incidence of flour albus in D-III Midwifery students at the Indonesian Strada Institute of Health Sciences.Methods: This study uses a pre-experimental method with the type of research design is one group pre test post test. The population in this study were all D-III Midwifery students at the Indonesian Strada Institute of Health Sciences and the sample was taken using a purposive sampling method with a total of 30 respondents. The data analysis technique used to test the hypothesis is the Wilcoxon test and data collection using a questionnaire.Results: The results of data analysis showed that the significance level was 0.000 < = 0.05 so that H0 was rejected and H1 was accepted. Thus, there was an effect of giving turmeric and honey boiled water to the occurrence of flour albus in D-III Midwifery students at IIK Strada Indonesia.Conclusion: There is an Effect of Giving Turmeric and Honey Boiled Water on the Incidence of Flour Albus in D-III Midwifery Students at IIK Strada Indonesia